Sustainable green technology for recovery of cotton fibers and polyester from textile waste. (1st May 2020) - Yousef, Samy; Tatariants, Maksym; Tichonovas, Martynas; Kliucininkas, Linas; Lukošiūtė, Stasė-Irena; Yan, Libo
Abstract: Waste jeans represent one of the major fractions of textile waste that is generated in millions of tons annually. Waste jeans are classified as a cotton-rich material, which can potentially become a sustainable source of raw cotton for production of new goods to tackle the shortage in cultivated cotton. In this framework, present research aims to develop a sustainable green technology for recovery of cotton fibers and polyester from textile waste. The first stage of the technology was concerned with removal of textile dyes from waste jeans using nitric acid leaching (conc. <60%) followed by the regeneration of the spent acid by activated carbon. After that, polyester was dissolved and separated from cotton by using a green switchable hydrophilicity solvent. To extract the polyester and regenerate the solvent, CO2 was added to the solution after mixing with distilled water at 0 °C for 1 h; the solidified polyester was collected by filtration, and the form of solvent was switched back to hydrophobic through heating and corresponding CO2 removal. Morphology and composition of the liberated fibers and extracted polyester were investigated using optical microscopy, SEM, and FITR. Regenerated solvent and acid were examined using FTIR and titration-based analysis. Performance of the proposed technology was studied based on the principles of circular economy and included determining of recycling rates, economic evaluation, greenhouse gas emissions estimates, and sustainability of the consumed and recovered materials. The results showed possibility of reaching economic returns up to 1, 629 $/ton of waste and reduction of carbon footprint by −1, 440 kg of CO2-eq/ t of waste. Graphical abstract: Image 10942580 Highlights: Leaching treatment was used to remove dyes from textile waste. Activated carbon was used to regenerate the spent leaching solutions. Switchable hydrophilicity solvent was used to liberate cotton fibers. Polyester was extracted from the solution by CO2 saturation of water at 0 °C. Recycling rate was 96% and economic returns were up to 1, 629 $/ton.